Pengaruh Metode Mind Mapping Dalam Peningkatan Hasil Belajar Siswa Pada Mata Pelajaran Sejarah Kebudayaan Islam Di Kelas IV MIS Banda Masen: The Effect of Mind Mapping Method in Improving Student Learning Outcomes in Islamic Cultural History Subjects in Class IV MIS Banda Masen - Wahyuni, Rita (PUSDATIN Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2025)
The purpose of the study was to find out how the students' learning outcomes in the SKI subject of the Hijrah of the Prophet Muhammad SAW to Habasyah and Thaif before using the mind mapping method in class IV MIS Banda Masen. How is the application of the mind mapping method in the SKI subject of the Hijrah of the Prophet Muhammad SAW to Habasyah and Thaif before using the mind mapping method in class IV MIS Banda Masen To find out whether student learning outcomes in the SKI subject of the Hijrah of the Prophet Muhammad SAW to Habasyah and Thaif increased after applying the mind mapping method in class IV MIS Banda Masen. This research is a Classroom Action Research (PTK) with a qualitative approach carried out in two cycles. Each cycle consists of planning, action implementation, observation, and reflection stages. The research subjects were 30 fourth grade students in the even semester of the 2023/2024 school year. Data collection techniques used tests (pre-test and post-test), observation, interviews, and documentation, while data analysis was carried out through data reduction, data presentation, and conclusion drawing. The results showed a significant increase in student learning outcomes. In the pre-cycle, the percentage of student learning completeness was only 23.33% with an average score of 52.41. After learning actions with the mind mapping method, learning completeness increased to 53.33% in cycle I and reached 86.67% in cycle II with a final average score of 83.16. This increase was also followed by changes in student behavior which were more active, enthusiastic, and focused in the learning process. Thus, it can be concluded that the application of mind mapping method is effective in improving learning outcomes and active participation of students in SKI learning.